TINJAUAN YURIDIS TANGGUNG JAWAB KOMISI PEMLIHAN UMUM (KPU) DALAM MENINGKATKAN PARTISIPASI MASYARAKAT PADA PEMILIHAN UMUM SERENTAK - Oloan Swandy Panjaitan; Erdianto Erdianto; Davit Rahmadhan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
As an example of a case that is still being debated regarding the rules and sanctionsthat must be stipulated, namely the case of the Tira Persikabo football team which promotedan online gambling site called SBOTOP on its jersey, that as explained in the regulationsregarding gambling above, this clearly violated the regulations regarding gambling. containedin Article 27 paragraph (2) in conjunction with Article 45 paragraph (2) of the 2008 ITE Lawwas amended into Law Number 19 of 2016 which does not allow people to make electronicinformation and documents that have gambling content accessible.There are two formulations of the problem in this study, namely First, what is thecriminal responsibility for the football team that promotes online gambling sites in their jersey?Second, what are the obstacles that impede criminal liability for a football team that promotesonline gambling sites in their jersey?There are 2 conclusions from this study, namely, First, the use of online gambling sponsors onthe Persikabo 1973 football jersey which competed in national competitions is part of agambling crime. Because these actions fulfill the entire set of elements contained in Indonesiancriminal law. The sponsorship of the online gambling site has complied with the provisions ofarticle 303 paragraph 1 which focuses more on the elements of making offers and providingopportunities for other people and/or the general public to gamble. In addition to theseprovisions, the act of sponsoring the gambling was also carried out through the Instagramsocial media of the Persikabo 1973 football club, so that it has fulfilled the elements of Article27 paragraph 2 of the ITE Law with the threat of imprisonment for a maximum of six yearsand/or a fine of up to one billion rupiah. Second, the obstacles in criminal liability for a footballteam that promotes online gambling sites on their jersey: a. The multiple interpretations of therules governing the prohibition of promoting online gambling sites on the jersey of theIndonesian football team. b. The absence of legal certainty by the National Police regardinglaw enforcement for football teams promoting online gambling sites at Jersenya.c. TheUncertainty of the Management of the Indonesian Football Association (PSSI) in ProhibitingFootball Teams in Indonesia from Promoting Online Gambling Sites. Suggestions from thisstudy are First, Law enforcement officials, in this case the police, must be active with thecommunity to immediately punish anyone involved in sponsoring online gambling sites inIndonesian football because it is a form of gambling crime that offers massive offers to allIndonesian people. through the media of football. Second, law enforcement officials must alsoeradicate all forms and practices of gambling because this is very dangerous for the life of theIndonesian nation and state because gambling can be the forerunner to the birth of othercrimes and is very contrary to public order, contrary to the values of and norms contained inthe life of society.Keywords: Accountability, Criminal, Football Team, Promoting, Online Gambling Site